The child support grant: the reported experiences of child support grant recipients - Seabi, Tshegofatso Martha (My University, 2015)
This study examined the reported experiences of the Child Support Grant recipients. The aim of this study was to find out how Child Social Grant recipients make sense of the Child Support Grant in their daily lives. How they make sense of their position in the society as recipients of the Child Support Grant. The factors that determine their participation and how they engaged when asked about the Child Support Grant. To understand how they make sense of receiving the grant compared to others and to compare the Child Support Grant recipients reported experiences with the stated aims of the Child Support Grant as stated in the policy documents. It came into view that Child Support Grant recipients according to their reported experience have or are currently facing tensions and paradoxes. As it was found that participants both believe themselves to be entitled to the Child Support Grant as such they are dependent on it. This entitlement and dependency is justified by the participants in that it gives them a sense of empowerment and independence for economic activity, hence their fears of losing the Child Support Grant. The Child Support Grant is considered very personal and participants agree that they need the security and stability that the grant offers to the them.